ANALISIS KINERJA ANGGARAN BELANJA MODAL DALAM LAPORAN REALISASI ANGGARAN (LRA) PADA KANTOR DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN ENDE - Wulandari, Atika; Marselina, Apriana; Ismail, Nuraini (Program Studi Akuntansi Universitas Flores, 2024)
The purpose of this study: 1. To determine the Performance of the Capital Expenditure Budget seen from the Expenditure Variance Analysis. 2. To find out the performance of the Capital Expenditure Budget seen from Expenditure Growth Analysis. 3. To find out the Performance of the Capital Expenditure Budget seen from the Expenditure Efficiency Ratio. This type of research is descriptive qualitative. The location of this research was carried out at the Public Works and Spatial Planning Office (PUPR) which is located on Jalan Banteng No. 1 Ende District. The data sources used are secondary data and primary data. Data collection techniques namely: Observation, Interview, Documentation and Literature Study. From analysis of spending variance, analysis of spending growth and spending efficiency ratios. It can be explained that: 1. The performance of the Capital Expenditure Budget is seen from the Expenditure Variance Analysis For 2022 the performance has decreased, 2. The Performance of the Capital Expenditure Budget can be seen from the Growth of Shopping Despite the growth in defense nja has fluctuated and in 2021 the growth is negative. 3. Budget performance can be seen from the Expenditure Efficiency Ratio From 2018 – 2022 the realization of the capital expenditure budget does not exceed the capital expenditure budget, this shows that the Office of the Ende Regency Public Works and Spatial Planning has made savings on the budget.